PROFESSIONAL KNOWLEDGE AND LEADERSHIP QUALITIES TRAINING TENDENCY BASED ON ACMEOLOGICAL APPROACH OF FUTURE TEACHERS (American Journal of Pedagogical and Educational Research, 2024)
The article examines the concept of "acmeological competence" as a factor in the development of leadership qualities of a future teacher. The concepts of "acmeological competence", "leadership", "leader" and "leadership qualities" are defined. Theories of scientists on the problem of developing leadership and leadership qualities of the teacher are presented. The role of forming acmeological competence in the development of teacher's leadership qualities is also noted.